Failure Factors in Agile Software Projects in SME Orgainzations (Albayan Scientific Journal, 2023)
In this research, we explored the use of Agile methods in small and medium-scale software development organizations. Specifically, focusing on three different types of agile approaches which are: Extreme Programming (XP), Scrum Methodology, and Dynamic System Development Methods. Most of the development methods and techniques are not employed as is, due to various constraints, including lack of budget, time, and personnel, amongst others. Existing development methods are adopted based on different factors, including project characteristics, development teams, and users. However, only 1 hypothesis was supported out of a total of 12, identifying one significant factor that can cause a failure, which is the large size of the organization, besides identifying a new failure attribute, which is losing control over the work.
Keywords: Agile Methods; Failure Factors; Adopting Agile in Organizations